Generalized design of high performance shunt active power filter with output LCL filter - Tang, Yi (2013)
This paper concentrates on the design, control, and implementation of an LCL-filter-based shunt active power filter (SAPF), which can effectively compensate for harmonic currents produced by nonlinear loads in a three-phase three-wire power system. With an LCL filter added at its output, the proposed SAPF offers superior switching harmonic suppression using much reduced passive filtering elements. Its output currents thus have high slew rate for tracking the targeted reference closely. Smaller inductance of the LCL filter also means smaller harmonic voltage drop across the passive output filter, which in turn minimizes the possibility of overmodulation, particularly for cases where high modulation index is desired. These advantages, together with overall system stability, are guaranteed only through proper consideration of critical design and control issues, like the selection of LCL parameters, interactions between resonance damping and harmonic compensation, bandwidth design of the closed-loop system, and active damping implementation with fewer current sensors. These described design concerns, together with their generalized design procedure, are applied to an analytical example, and eventually verified by both simulation and experimental results.